The Use of Zinc Oxide (ZnO) Photocatalyst for Photodegradation of Car Wash Wastewater - Abd Mujahid Hamdan; Rauza Azkiya; Arief Rahman; Mailiza Efriana; Rahmad Maulana; Hanif Hanif (Jurnal Fisika dan Aplikasinya, 2023)
Untreated motor vehicle waste has the potential to damage the environment. The photodegradation method can decompose pollutants with the help of UV-A light and photocatalysts. Zinc Oxide (ZnO) is a photocatalyst capable of degrading motor vehicle washing waste. This study aims to investigate the ability of ZnO as a photocatalyst in degrading pollutants in motor vehicle waste. The independent variables in the experiment were the mass of ZnO and the contact time. The variables used were mass 0.5, 0.75, and 1 gram with a contact time of 2, 3, and 4 hours. The experimental results showed that ZnO irradiated with UV-A lamp was able to degrade organic substances. The mass and contact time of ZnO affect the effectiveness of photodegradation. These results show that the use of ZnO photocatalyst for photodegradation of Carwash Wastewater may be future technology to treat car wash wastewater.